ANALISIS PERBANDINGAN DATA BATIMETRI HASIL PENGUKURAN MULTIBEAM ECHOSOUNDER DAN SINGLEBEAM ECHOSOUNDER UNTUK WILAYAH PERAIRAN DANGKAL - , RAHMAT SIDIK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bathymetric survey is series of activities carried out to determine the condition of seafloor topography. This activity has been widely used in the field of marine, for example in determining safe cruise lines, planning the construction of beachside buildings, detecting the occurrence of potential tsunami in a certain area, offshore oil exploration and other engineering practices. As the advancement of bathymetric surveying, there are several methods and technologies that usually used. Two of those technologies that utilize acoustic waves to obtain depth data are singlebeam echosounder (SBES) and multibeam echosounder (MBES). The difference between these bathymetric data acquisition devices needs to be studied further so that they can be used as a basis to determine the level of difference in the value of the depth of both types of these devices. Bathymetric data acquisition process that utilize SBES ODOM Echotrac DF3200 with has low frequency and MBES Seabeam ELAC 1050D with has high frequency for shallow water areas will provide different data on depth (Z) even thought at the same positions (X, Y) due to the difference types and frequency of the devices. Therefore, statistical tests are required to present an overview on the differences between both devices in shallow waters by the 95% confidence level. Prior to the comparison test, the bathymetric data obtained from SBES and MBES must meet the quality standards. Bathymetry data quality standards have been set in the International Hydrographic Organization (IHO) SP-44 5th Edition 2008 and SNI 7646 in 2010. Based on the quality test on depth of SBES, it is found that the result of the measurements had been obtained in accordance with the determined standards. The comparison test conducted by using the Z test for 95% level of confidence shows that the value of Z computed (Z0) is -0.35. From that result, the Z0 value is within the range of -1.96 < Z0 < 1.96. Therefore, we may conclude that the measurement results of SBES and MBES for shallow waters are not significantly different. In other words, the quality of MBES data meets the required quality standard